Maximum strength development and volume-load during concurrent high intensity intermittent training plus strength or strength-only training - Panissa, Valéria L. G. (2018)
The purpose of this study was to compare maximal strength gains during strength training (ST) and concurrent training (CT) consisting of high-intensity intermittent training plus strength training over the course of a 12-week intervention. A secondary purpose was to examine the relationship between strength training volume and strength gain in both groups. Nineteen recreationally active males were divided into CT (n = 11) and ST (n = 8) groups. The CT group performed repeated 1 min efforts at 100% of maximal aerobic speed interspersed by 1 min of passive recovery until accumulating a total running distance of 5km followed by a strength session (consisting of three sets of seven exercises with loads of 8-12 repetition maximum) twice weekly for a period of 12 weeks. The ST group performed only strength training sessions during the same 12-week period. Strength training total volume-load (Σ repetitions × load) for the upper-and lower-body was computed, while maximal strength (1RM) was evaluated at baseline, week 8, and week 12. Lower-body volume-load over 12 weeks was not different between groups. Absolute 1RM increased in both groups at week 8 and week 12, while 1RM relative to body mass increased in both groups at week 8, but only ST increased relative maximum strength between week 8 and week 12. There was a statistically significant correlation between strength training lower-body volume-load and maximum strength change between baseline and week 8 for the CT group (r = 0.656), while no significant correlations were found for the ST group. In summary, executing high-intensity intermittent exercise twice a week before strength training did not impair maximal strength after 8 weeks, however, only ST demonstrated an increase in relative strength after 12 weeks.